Adaptive active frequency support strategy for receiving-end MMC-HVDC stations based on rate of change of frequency - Tian, Baoye; Li, Junjie; Zhai, Hefeng; Zhang, Ye (Frontiers in Electronics, 2025)
As the proportion of HVDC infeed power increases in the eastern receiving-end power grid, inertia and frequency regulation capability decrease. Utilizing modular multilevel converter (MMC) stations at the receiving-end to provide active frequency support can effectively address this challenge. To this end, this paper first introduces conventional control methods for MMC-based HVDC systems participating in frequency regulation. Subsequently, it establishes a critical mapping relationship between the initial rate of change of frequency (RoCoF) and the subsequent maximum frequency deviation at the converter bus. Building upon this relationship, an adaptive strategy for dynamically adjusting the frequency regulation parameters (virtual inertia and damping coefficient) of the MMC is proposed. This strategy enables the MMC to provide prioritized inertia support during the initial inertial stage and switch to damping support during the recovery stage. Finally, simulations conducted on a modified IEEE 39 bus system validate the effectiveness of the proposed adaptive frequency regulation strategy.